Pengaruh Harga Bauran Pemasaran Nutrisari terhadap Minat Beli Konsumen Kantin Kampus STIE YPBI - Nahason Sitohang; Hildegardis Jeni Tefa (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the effect of price as a component of the marketing mix of NutriSari products on consumers’ purchase intention at the STIE YPBI Campus Canteen. Price is a crucial element of the marketing mix that directly influences consumer perceptions and purchasing decisions. Therefore, understanding consumers’ price perceptions is essential for companies in developing effective marketing strategies and maintaining competitiveness. This research employed a quantitative descriptive approach, with data collected through questionnaires distributed to consumers at the STIE YPBI Campus Canteen. The population of this study consisted of 40 active consumers within the campus canteen environment. Data were analyzed using validity and reliability tests, normality testing, simple linear regression analysis, t-test, and F-test with the assistance of SPSS software. The results indicate that price has a significant effect on purchase intention, as evidenced by an F-test value of 5.440 and a coefficient of determination of 54.40%. This finding implies that 54.40% of consumers’ purchase intention is influenced by price, while the remaining percentage is affected by other factors not examined in this study. Furthermore, the t-test results show that the calculated t-value (2.332) is greater than the critical t-value (2.024), indicating a positive and significant effect of price on purchase intention. The indicators of price affordability, price-quality suitability, price competitiveness, and price-benefit suitability collectively contribute to increasing consumers’ purchase intention at the STIE YPBI Campus Canteen.